Study of Iron Deficiency Levels among Pregnant Women Attending the Obstetrics Golden Complex Clinic, Sirte - Munay Deekari; Hana Zaed (AlQalam Journal of Medical and Applied Sciences, 2025)
Iron deficiency anemia (IDA) is a major public health concern among pregnant women, associated with adverse maternal and fetal outcomes. During pregnancy, iron requirements increase substantially, and failure to meet these demands can result in anemia, fatigue, and impaired immune function. This study was conducted to assess the prevalence of iron deficiency among pregnant women in Sirte city, Libya, and to examine its association with age, abortion history, menstrual cycle length, and parasite infection status. A cross‑sectional study was conducted between July and August 2024 involving 120 pregnant women attending Golden Complex Clinic and Al‑Ghad Clinic. Serum iron levels were measured using the Mindray CL‑1200i analyzer and categorized as <12 ng/ml, 12–15 ng/ml, and >15 ng/ml. Data were analyzed using SPSS version 25, with descriptive statistics and Chi‑square tests applied; p<0.05 was considered significant. Overall, 80.8% of participants had iron levels <12 ng/ml, 18.3% were between 12–15 ng/ml, and only 0.8% exceeded 15 ng/ml. The highest prevalence of deficiency was observed in the 20–25-year age group (32.5%). Women with a history of abortion showed 25% deficiency compared to 55.8% among non‑abortion cases. Iron deficiency was also prevalent among women with shorter menstrual cycles (49.1% in 5‑day cycles vs. 31.6% in 6–11-day cycles) and among those with parasite infections (26.6%). The study revealed a high prevalence of iron deficiency among pregnant women in Sirte city, with significant associations across age, reproductive history, menstrual cycle, and infection status. These findings underscore the urgent need for nutritional interventions, health education, and integrated strategies to address iron deficiency and improve maternal health outcomes.